Improving the energy density of Li-ion capacitors using polymer-derived porous carbons as cathode - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Electrochimica Acta, 2014)
High energy density Li-ion hybrid electrochemical capacitors (Li-HEC) are fabricated with 3 D architectured high surface area porous carbon (HSPC) derived from the poly(acrylamide-co-acrylic acid) potassium salt in a single step without any activating agent. The obtained HSPC exhibits high specific surface area of 1490 m(2) g(-1) and characterized with several analytical techniques. Li-HEC is fabricated with insertion type Li4Ti5O12 anode by adjusting the mass balance based on the single electrode performance with Li. The Li-HEC delivered the maximum energy density of similar to 55 Wh kg(-1), which is much higher than commercially available activated carbon (similar to 36 Wh kg(-1)). Further HSPC based Li-HEC delivered excellent cycleability and rendered similar to 87% of initial value after 2000 cycles. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: energy density; Li-ion hybrid electrochemical capacitors; non-aqueous; porous carbon

Hexaaminobenzene derived two-dimensional polymer supercapacitor with high specific capacitance and energy density - Wakchaure, Vivek C.; Kottaichamy, Alagar R.; Nidhankar, Aakash D.; Ranjeesh, Kayaramkodath C.; Nazrulla, Mohammed A.; Thotiyl, Musthafa O.; Babu, Sukumaran S. (ACS Applied Energy Materials, 2020)
Recent research interest has been shifted toward energy storage devices, especially supercapacitors, which provide high specific power and long cycle life. In this context, two-dimensional organic polymers are a class of versatile materials found to be useful in energy storage applications. However, the performance is not promising due to the low capacitance, energy density, and cyclic stability. Here, we report a two-dimensional polymer derived from hexaaminobenzene and pyromellitic dianhydride and its excellent supercapacitor performance. The specific capacitance of the two-dimensional polymer is found to be 805 F g(-1) at 0.5 A g(-1) current density in galvanostatic charge-discharge, which is the highest among the organic twodimensional polymer and most of the carbon-based materials. The superior performance of the 2D-polymer compared to a model derivative (350 F g(-1) at 0.5 A g(-1) current density) points to the critical role of a 2D-platform to excel. The high energy density, excellent cyclic stability, and low self-discharge rate support the 2D-polymer supercapacitor as a promising candidate for futuristic applications.
Keywords: 2D-polymer; energy density; Energy storage; hexaaminobenzene; supercapacitor